The Agriculture-Nutrition Disconnect in India: What Do We Know? - Gillespie, Stuart; Harris, Jody; Kadiyala, Suneetha (International Food Policy Research Institute, 2012)
India is home to one-third of the world’s malnourished children. This figure that remains stubbornly high, despite the country having the second-fastest growing economy in the world, with agriculture accounting for a significant part of that growth. Agriculture continues to be the primary source of livelihood for the majority of nutritionally vulnerable households in India. In order to maximize the nutrition-sensitivity of agriculture, we need to first map existing evidence of the various links, pathways and disconnects between agriculture and nutrition. We start with a narrative review of the background literature for India, including an assessment of trends in nutrition and agriculture indicators. A conceptual framework is then put forward to aid in the systematic search for links and disconnects, delineating seven key pathways between agriculture and nutrition. Evidence is then mapped to these pathways through a summary of the literature for each pathway as well as a fully annotated bibliography.